Human αβ and γδ T Cells in Skin Immunity and Disease - Cruz, Michelle S.; Diamond, Alani; Russell, Astrid; Jameson, Julie Marie (Frontiers in Immunology, 2018)
γδ T lymphocytes maintain skin homeostasis by balancing keratinocyte differentiation and proliferation with the destruction of infected or malignant cells. An imbalance in skin-resident T cell function can aggravate skin-related autoimmune diseases, impede tumor eradication or disrupt proper wound healing. Much of the published work on human skin T cells attributes T cell function in the skin to αβ T cells, while γδ T cells are an often overlooked participant. This review details the roles played by both αβ and γδ T cells in healthy human skin and then focuses on their roles in skin diseases such as psoriasis and alopecia areata. Understanding the contribution of skin-resident and skin-infiltrating T cell populations and cross-talk with other immune cells is leading to the development of novel therapeutics for patients. However, there is still much to be learned in order to effectively modulate T cell function and maintain healthy skin homeostasis.